Associação entre a qualidade na tomada de decisão ao longo do dia no Iowa Gambling Task e as emoções básicas - Daniel Hosken Pires (2022)
The decision-making process involves choosing at least one among some alternatives in situations involving uncertainty. Every day we make thousands of decisions that range from more everyday choices, like what to eat for lunch, what music to listen to, to choices that can change the course of our lives, like which college to enroll in or where to invest our money. In addition, in some moments we do not choose deliberately, with a high level of awareness during the process, that is, the decision occurs with greater relevance of more automatic, unconscious mechanisms. The act of decision involves several cortical processes that both consciously and unconsciously assess the possible consequences and the risk involved in each of them. This work aims to evaluate the cognitive performance of two groups of volunteers playing the Iowa Gambling Task (IGT) alone at different times of the day (morning and afternoon) and the possible difference in the primary emotional response related to this performance. A platform for data collection via the web was developed. The platform hosts the IGT game in the foreground, and in the background it collects data on the individual's performance and captures images of their face throughout the entire game. The data collected allowed us to carry out analyzes that were divided into: (i) analysis of performance in the IGT game in the two periods of the day; (ii) behavior analysis of basic emotions and emotional valence in the two periods of the day; (iii) behavior analysis of basic emotions and emotional valence in relation to game performance. Performance was also analyzed based on the variables: sex, hours of sleep, playing time and age. The results found showed statistical differences in basic emotional responses (i) in the groups separated by sex, where it was possible to perceive in the general performance the presence of more detectable expressions of fear and surprise in women. (ii) In the groups separated by performance, it was possible to observe the presence of more detectable surprise expression in the disadvantageous result group. These results suggest a behavioral response, resulting from a physiological manifestation related to the undesired result.